2006
DOI: 10.1124/jpet.106.101808
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin, an Inhibitor of Hsp90, Potentiates Cytochrome P4502E1-Mediated Toxicity in HepG2 Cells

Abstract: Cytochrome P450 2E1 (CYP2E1) potentiates oxidative stressmediated cell death. Heat shock proteins (Hsps) modulate the stability and function of numerous proteins. We examined the effect of geldanamycin (GA), an inhibitor of Hsp90, on CYP2E1-mediated toxicity in transfected HepG2 cells overexpressing CYP2E1 (E47 cells). Basal expression of CYP2E1 and Hsp90 was higher in E47 cells compared with control C34 cells, which do not express CYP2E1. Treatment with GA resulted in significant toxicity to E47 cells compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Ethanol was found to compromise this interaction between Hsp90 and CYP2E1, resulting in increased levels of CYP2E1 protein expression, which can damage the liver cells through its nitroxidative stress-mediated events [148]. These results are consistent with the inhibition of Hsp90 by geldanamycin, which increased CYP2E1-mediated toxicity in HepG2 hepatoma cells [149, 150]. Since both acute binge and chronic ethanol administration also promote hepatic protein nitration, it would be interesting to evaluate whether Hsp90 is nitrated in these alcohol-exposure models and whether this nitration leads to hepatic injury directly or indirectly through interference of binding between nitrated Hsp90 and CYP2E1, leading to its elevation.…”
Section: Functional Consequences Of Protein Nitration In Acute Andmentioning
confidence: 79%
“…Ethanol was found to compromise this interaction between Hsp90 and CYP2E1, resulting in increased levels of CYP2E1 protein expression, which can damage the liver cells through its nitroxidative stress-mediated events [148]. These results are consistent with the inhibition of Hsp90 by geldanamycin, which increased CYP2E1-mediated toxicity in HepG2 hepatoma cells [149, 150]. Since both acute binge and chronic ethanol administration also promote hepatic protein nitration, it would be interesting to evaluate whether Hsp90 is nitrated in these alcohol-exposure models and whether this nitration leads to hepatic injury directly or indirectly through interference of binding between nitrated Hsp90 and CYP2E1, leading to its elevation.…”
Section: Functional Consequences Of Protein Nitration In Acute Andmentioning
confidence: 79%
“…The effect of GA treatment on endocytosis was independent of oxidative stress Previous reports have suggested that the effect of GA on cells could be due to oxidative stress generated during the metabolism of the quinone group within the drug by cytochrome P450 (Billecke et al 2002;Dikalov et al 2002;Dey and Cederbaum 2006). To address whether or not the effect of GA on transferrin endocytosis is related to oxidative stress, cells were incubated with radicicol (RD), another inhibitor of the Hsp90 family, which lacks the quinone group and, therefore, does not generate an oxidative stress (Schulte et al 1999;Billecke et al 2002;Sreedhar et al 2003).…”
Section: Resultsmentioning
confidence: 97%
“…Glutamate activates the Ras/Raf/MEK/ERK cascade, and accelerates RPE cell proliferation [26]. Many proteins associated with cell structure and cell motility were also upregulated, including PLOD2 (procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2), Moesin, Cofilin-1, FBXL17 (F-box and leucine-rich repeat protein 17) and CAPZA2 (F-actin capping protein subunit alpha-2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hsp90 protects against CYP2E1-dependent oxidant stress in HepG2 cells [26]. HSP90 inhibitors can induce oxidative stress in RPE cells and other cells, including radicicol and GA [34].…”
Section: Discussionmentioning
confidence: 99%